EPISTEMIC-DEMOCRATIC TENSION IN THE BOTTOM-UP GOVERNANCE OF ALGORITHMS - Cotter, Kelley (AoIR Selected Papers of Internet Research, 2025)
The governance of platform algorithms presents a critical challenge as these technologies increasingly pose threats to privacy, agency, fairness, and equity, often reenacting and mediating existing power systems. Traditional governance models, primarily top-down approaches led by policymakers and private corporations, are essential yet insufficient. This paper argues for the incorporation of "bottom-up governance," focusing on the "epistemic-democratic tension" (Krick, 2022) between inclusive participation and expertise-based decision-making. I argue that to ensure that algorithms function fairly and justly for all, bottom-up governance requires involving and taking seriously “lay” experts. Bottom-up governance extends beyond merely soliciting input from citizens on algorithms; it necessitates recognizing the authority of non-technical knowers and privileging subjugated standpoints.